2002
DOI: 10.1067/mva.2002.125032
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm repair with the Zenith stent graft: Short to midterm results

Abstract: The Zenith device is safe, versatile, and effective in the short to medium term. Most patients need wide stent grafts (>or=28 mm proximally and >or=16 mm distally) to achieve 10% to 20% oversizing to prevent type I endoleak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 6 publications
1
47
0
2
Order By: Relevance
“…As a result, preventing AKI is crucial in improving outcome, especially in populations at high-risk, such as those undergoing EVAR. The predictive factors of AKI after elective EVAR are not well determined, as the randomized studies have not reported AKI-incidence and the majority of case-series have not used a consistent AKI definition (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, preventing AKI is crucial in improving outcome, especially in populations at high-risk, such as those undergoing EVAR. The predictive factors of AKI after elective EVAR are not well determined, as the randomized studies have not reported AKI-incidence and the majority of case-series have not used a consistent AKI definition (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…La ausencia de complicaciones relacionadas a la prótesis en el mediano plazo reafirma las cualidades de las endoprótesis actuales en el tratamiento endovascular de los aneurismas aórticos abdominales en los casos adecuadamente seleccionados, de acuerdo a las condiciones anatómicas exigidas por el fabricante 13 . Sin embargo, hemos observado en cinco pacientes la presencia de una trombosis laminar mural dentro del cuerpo principal de la endoprótesis que no impide el flujo sanguíneo hacia distal, que aparece ya en los primeros controles de Angio scanner y se mantiene en el tiempo.…”
Section: Discussionunclassified
“…Az említett szövődmé-nyek tehát nem a műtétek következményei, hanem a beavatkozást indikáló kórképek következményei voltak (malperfúziós szindróma B típusú dissectióban). Hazai adataink hasonló arányokat mutatnak az elérhető nemzetközi irodalomban leírtakhoz, ahol e két ritka szövőd-mény előfordulása 5% alatti [20,21].…”
Section: Megbeszélésunclassified